PENGARUH LATIHAN PLYOMETRIK TERHADAP KECEPATAN TENDANGAN LURUS PENCAK SILAT - Satria Pratama, - (2022)
This study aims to determine whether plyometric exercises Squat Split Jump and Stride Jump Crossover have a significant effect on the speed of straight kicks in pencak silat. This study uses a true experimental method with a two-group pretest posttest design model. 20 extracurricular athletes of SMAN 1 Dayeuhkolot made research subjects with non-probability sampling techniques. All samples were pretested to determine the treatment group. The procedure of this research is to provide a Squat Split Jump exercise model and a Stride Jump Crossover exercise model. The data obtained were processed using SPSS Version 24. The results of the t-test of the experimental group 1 can be seen with a significance of 0.001 < 0.05. in the experimental group 2 can be seen the significance of 0.000 <0.05. then the calculation shows a significant difference. From the pretest data the average for group 1 is 16,846 seconds and group 2 is 16,70 seconds. and the average post test for group 1 was 12,243 seconds and group 2 was 13,128 seconds. From the results of the posttest comparison test of the 2 experimental groups, it is known that the significance is 0.460 > 0.05. Thus, it can be said that from the two training models, there is no significant difference between the Squat Split Jump training model and the Stride Jump Crossover training model in increasing the speed of straight kicks in pencak silat.